(untitled) (Journal of actual problems of jurisprudence, 2018)
The author of the article gives a comparative research of the legislations of Russia and Kazakhstan, analyses the notion of malicious deviation from fine payment as the convict’s action who hasn’t paid the fine in the term confirmed by the criminal – executive law. As is known, the definition of a system of criminal sanctions based on the objectives and principles of criminal policy is a prerequisite for ensuring the effectiveness of the influence on the perpetrators of crimes and preventing the commission of new crimes, and ultimately – one of the important indicators of the effectiveness of the criminal- legal policy of the state. The choice of the best ways to improve the criminal law regulation of the fine and the legislation on the criminal enforcement of its enforcement will help realize the principle of the inevitability of this type of punishment. The fine is reasonably required in law enforcement practice and is quite effective in the process of counteraction to crimes of various categories. Key words: law, criminal law, criminal responsibility, state, fine, administrative responsibility, citizen, person, person.